Mechanism of phase formation in Pb(ZrxTi1-x)O3 synthesized by a partial oxalate method - Leite, Edson R.; Cerqueira, Marinalva; Perazoli, Lenig A.; Nasar, Ricardo S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Wiley, 1996)
The phase formation mechanism, as well as the morphotropic phase boundary, of lead zirconate titanate (PZT) processed by a partial oxalate method was investigated by simultaneous thermal analysis (TG-DTA) and by qualitative and quantitative X-ray diffraction (XRD). The results show that the ZrxTi1-xO2 (ZT) phase reacts with PbO forming the PZT phase without intermediate phases. XRD analysis showed the coexistence of rhombohedral and tetragonal phases for 0.47 ≤ x ≤ 0.55 with the phase boundary composition for x = 0.51. For low calcination temperatures, preferential formation of the PZT rhombohedral phase was observed. A model for phase formation of PZT by the partial oxalate method is proposed based on the existence of two interfaces of reaction (PbO-PZT and PZT-ZT) and diffusion of cations.
Keywords: Calcination; Differential thermal analysis; Diffusion; Interfaces (materials); Ions; Phase composition; Phase transitions; Synthesis (chemical); Thermal effects; Thermogravimetric analysis; X ray diffraction; Calcination temperature; Lead zirconate titanate; Morphotropic phase boundary; Partial oxalate method; Phase formation; Rhombohedral phase; Simultaneous thermal analysis; Tetragonal phase; X ray fluorescence; Lead compounds